Dark sky [large type] - Box, C. J. (Box, C. J. Joe Pickett novel, 2021)
The governor of Wyoming gives Joe the thankless assignment of taking a tech baron on an elk hunting trip. Unbeknownst to them, a man-hunter is hot on their heels. Finding himself without a weapon, a horse, or a way to communicate, Joe must rely on his wits and his knowledge of the outdoors to protect himself and his charge. Meanwhile, when Joe's closest friend, Nate Romanowski, and Joe's daughter Sheridan learn of the threat to his life, they follow him into the woods to try and rescue him before it's too late.